Exploring higher education governance in Poland and Romania: Re-convergence after divergence?. (September 2017) - Dobbins, Michael
This analysis focuses on changes in higher education governance in Poland and Romania in the post-communist era. The author applies a theoretical framework based on institutional isomorphism and historical institutionalism and maps the policy trajectories of both systems on the basis of three governance ideal-types. The public higher education systems of both countries initially took a markedly different reform path after 1989. Polish higher education by and large returned to its historical model of 'academic self-rule' and has resisted pressures for stronger marketization, even during the Bologna Process, while Romania has been characterized by an early and strong isomorphic orientation towards higher education models primarily of Anglo-American inspiration. The main argument of the paper is that – after a period of marked divergence – both systems are visibly 're-converging' towards a new hybrid governance model. The new governance model aims to (re-)embed the research mission of universities to foster homegrown research and innovations. These new hybrid constellations enable both countries to simultaneously deal with global pressures for change and liberate themselves from economic dependence on the West, while not throwing historical institutions entirely overboard.